Transforming fire prevention: a case study. Issue 2 (18th May 2015) - Higgins, Emma; Taylor, Mark; Francis, Hulya; Jones, Mark; Appleton, Deb
Abstract : Purpose: – The purpose of this paper was to examine the transformation of fire prevention processes via improved targeting of fire prevention interventions over a four-year period. Design/methodology/approach: – A four-year case study of the transformation of fire prevention processes involving a UK fire and rescue service, local council, National Health Service primary care trust and a police force was undertaken. Findings: – Understanding the socio-economic causal factors underlying unintentional dwelling fires, and the need to work in collaborative partnerships to achieve change in such factors can support more targeted and effective fire prevention activities. Research limitations/implications: – Analysis of underlying causal factors and their relationships, together with population segmentation and working in coordinated collaborative partnerships, can support enhanced fire risk assessment and community safety. This supported more pro-active early intervention fire risk management. Practical implications: – Analysis of socio-economic causal factors and socio-economic groups associated with unintentional dwelling fires can assist in targeting fire prevention activities in a more effective and efficient manner. This enabled the fire and rescue service to target fire prevention to social groups most at risk of dwelling fires and the types of fires (for example, kitchen fires) relevant to the different social groups. Social implications: – Collaborative public sector partnerships can achieve change in the socio-economic circumstances of at-risk individuals to support fire prevention. This enables the social- and health-related factors underlying fire risk to be addressed by the relevant partner health or social services agencies. Originality/value: – The detailed analysis of the transformation of fire prevention activities that led to an implemented approach to enhance community safety. In particular, the analysis and evaluation of the move to collaborative multi-agency partnerships to support and improve fire prevention activities.